Policy atlas on food and nutrition security and resilience: Burkina Faso - Marivoet, Wim; Ulimwengu, John M.; Sall, Leysa Maty (International Food Policy Research Institute, 2020)
This report is the final outcome of various knowledge products and training material, usually labelled as “printed eAtlas”, which have been developed and shared with Civil Society Organizations (CSOs) under the Voice for Change Partnership (V4CP) programme.